The Values of Systemic Immune-Inflammation Index and Neutrophil–Lymphocyte Ratio in the Localized Prostate Cancer and Benign Prostate Hyperplasia: A Retrospective Clinical Study - Wang, Shuo; Ji, Yongpeng; Chen, Yanyun; Du, Peng; Cao, Yudong; Yang, Xiao; Ma, Jinchao; Yu, Ziyi; Yang, Yong (Frontiers in Oncology, 2022)
Purpose To evaluate the diagnostic values of systemic immune-inflammation index (SII) and neutrophil-lymphocyte ratio (NLR) in patients with localized prostate cancer (PCa). Methods Between January 2014 and December 2019, 117 patients with benign prostate hyperplasia (BPH) and 278 patients with localized PCa who underwent radical prostatectomy (RP) were included into this study. The inflammatory markers including SII, NLR, platelet-lymphocyte ratio (PLR), lymphocyte-monocyte ratio (LMR), lymphocyte ratio (LR), neutrophil ratio (NR), mean platelet volume (MPV) and red cell distribution (RDW) of these two groups were examined and analyzed. ROC curve analysis was performed to assess the discriminative ability of inflammatory markers and their combination with tPSA for PCa. The binary logistic regression model was used to evaluate the association between significant inflammatory markers and risk of PCa. Results The pathological results from RP specimen comprised 72 (25.90%) patients with pT1, 168 (60.43%) patients with pT2 and 38 (13.67%) patients with pT3. According to Student’s t test, patients with PCa had higher NLR (P=0.034), SII (P=0.008), NR (P=0.004) and lower LR (P=0.025), MPV (P=0.003), TPV (p=0.022) compared with patients with BPH, the distribution of age, PLR, LMR, RDW, f/t PSA ratio and BMI did not show any significant differences. The AUC for NLR, SII, NR and tPSA was 0.697 (P=0.015), 0.719 (P<0.001), 0.647 (P=0.009) and 0.708 (P<0.001), with the threshold values of 1.6, 471.86, 65.15% and 12.89ng/mL, respectively. Patients were divided into two groups according to the threshold values, respectively. By using the multivariable logistic regression models, NLR ≥ 1.6 (OR, 2.731; 95% CI, 0.937-7.961, P=0.042), SII ≥ 471.86 (OR, 1.274; 95% CI 0.473-3.433; P=0.033) and PSA ≥ 12.89 ng/mL (OR, 1.443; 95% CI, 0.628-3.944; P=0.014) were independent risk factors associated with PCa. The AUC for combination of NLR, SII and NR with tPSA were 0.705 (P<0.001), 0.725 (P<0.001) and 0.704 (P<0.001), respectively. Conclusion This study demonstrated that SII, NLR and NR were all independent risk factors of PCa. In addition, SII is a more powerful tool among these three inflammatory markers associated with PCa. Besides, combination of SII and NLR with tPSA had no too much advantage compared with themselves alone..